The Effect of Personal Selling, Social Media Advertising and Sales Promotion on Purchasing Decision : Case at Orbit Telkomsel Sumbagteng Region - Anta Pratama Ginting; Indrawati Indrawati (Digital Innovation : International Journal of Management, 2024)
Telkomsel Orbit is a product that provides an internet network that can be used anytime and anywhere, thereby attracting consumer interest. The company continues to market and develop this product so that it can continue to compete with other similar products, including by implementing several marketing methods which will be studied in this research. This study seeks to examine the impact of the independent variables, namely (X1) Personal Selling, (X2) Social Media Marketing and (X3) Sales Promotion on the dependent variable (Y1) Purchasing Decisions. This study uses quantitative data collected based on filling out questionnaires carried out by 330 respondents who are users of Telkomsel Orbit products in the Central Sumatra Region. Sampling was carried out by purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) techniques via the SmartPLS application. Statistical results show that the independent variables, such specifically as (X1) Personal Selling, (X2) Social Media Marketing and (X3) Sales Promotion have a positive and substantial effect on the dependent variable (Y1) Purchase Decision resulting in an R-Square featuring the value of 0.267 or 26.7%. The Telkomsel Orbit marketing team is expected to continue to improve and evaluate the application of personal selling, social media marketing and sales promotions to influence consumer decisions in choosing Telkomsel Orbit products. The application of personal selling is considered the most effective in this research, so it is hoped that optimization of human resources and abilities in forming relationships with consumers will continue to be carried out. Likewise, sales promotions must be carried out more massively to be able to continue to compete with other competitors, because the best and most attractive price offers or sales promotion methods will be superior in influencing purchasing decisions. Meanwhile, social media marketing continues to be optimized, especially facing the digital world, where information is disseminated via the internet or social media, so content is needed with information content that can attract consumer interest in products.